2019
DOI: 10.1371/journal.pone.0213914
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic variation of spider monkey (Ateles geoffroyi) contact calls is related to caller isolation and affects listeners’ responses

Abstract: Group living animals produce vocalizations denominated “contact calls” to maintain contact with out-of-sight group members. These calls have been shown to vary with caller identity and distance to potential listeners. However, it is not clear whether the acoustic variation of contact calls is related to caller social isolation (e.g., inside or outside a subgroup) and listeners’ responses that can be helpful to maintain contact. Here, we addressed these questions in spider monkeys ( Ateles geoffroyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Primate vocal communication includes some very diverse acoustic outputs, ranging from low-frequency contact calls (e.g., spider monkeys— Ordóñez-Gómez et al. 2019 ) to elaborate vocal displays like songs (e.g.…”
mentioning
confidence: 99%
“…Primate vocal communication includes some very diverse acoustic outputs, ranging from low-frequency contact calls (e.g., spider monkeys— Ordóñez-Gómez et al. 2019 ) to elaborate vocal displays like songs (e.g.…”
mentioning
confidence: 99%
“…They could also be varying other aspects of their calls depending on the social context. For example, there is evidence that they are able to modify their calls as a function of the distance between callers and recipients, as individuals emitted and respond with low frequency whinnies when callers are outside a subgroup (separated by long distances) to facilitate vocal contact [33].…”
Section: Discussionmentioning
confidence: 99%
“…Ordóñez-Gómez et al . [33] showed that individuals even lower the fundamental frequency of whinnies to facilitate communication and to maintain contact with distant individuals (those traveling outside their subgroup). Social cohesion is also supported by Briseño-Jaramillo et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whinnies are loud enough to be audible by any member of a given subgroup and beyond [30]. Ordóñez-Gómez et al [33] showed that individuals even lower the fundamental frequency of whinnies to facilitate communication and to maintain contact with distant individuals (those traveling outside their subgroup). Social cohesion is also supported by Briseño-Jaramillo et al [34] showing that call-matching between two individuals is higher between preferred grooming partners, in line with the Dunbar's "grooming-at-distance" hypothesis [35].…”
Section: Introductionmentioning
confidence: 99%